STUDY OF POLYSACCHARIDE COMPLEX OF SORBARIA SORBIFOLIA LEAVES - M. E. Guschina; S. L. Adzhiakhmetova; E. T. Oganesyan (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have isolated polysaccharides and identified monosaccharides after hydrolysis during the work. Gravimetric analysis identifies the prevalence of pectin substances (PS) and hemicelluloses A (HC A).